The level of values-based leadership and its impact on job stability among teachers in Al Dhahirah Governorate schools in the Sultanate of Oman - Al-Balushi, Sheikha bint Bati; Al-Azri, Dr. Saif bin Nasser; Al-fawair, Dr. Ahmad Mohammed Jalal (Journal of Posthumanism, 2025)
This study aimed to explore level of values-based leadership and its impact on job stability among teachers in Al Dhahirah Governorate schools in the Sultanate of Oman. To achieve the study's objectives, a descriptive research methodology was employed. The study relied on a questionnaire as the primary tool for data collection, which consisted of 19 items distributed across three sections: demographic information, values-based leadership, and job stability. The validity and reliability of the instrument were confirmed. The questionnaire was administered to a random sample of 146 teachers from Al Dhahirah Governorate. The results indicated that the level of implementation of values-based leadership was high, and the level of job stability among the sample was also high. Linear regression analysis revealed that values- based leadership accounted for 66% of the variance in job stability among the teachers in the study sample. Based on these findings, several recommendations were proposed, most notably: enhancing human values in educational leadership through training programs; activating the role of the leader as a role model in professional conduct and discipline by adhering to administrative laws and regulations; and conducting future research on the impact of educational leaders’ commitment to values-related practices.